Neobladder creation is still a conduit to peritoneal dialysis – Successful use of peritoneal dialysis after invasive bladder cancer. Issue 4 (July 2022) - Cosmatos, Alexandre; McCormick, Brendan; Brown, Pierre Antoine
Peritoneal dialysis (PD) is as safe and more cost-effective than haemodialysis (HD). It also allows patients to undergo renal replacement therapy (RRT) from home. However, PD remains underutilised in many parts of the world. This is true in part because of many perceived relative contraindications to PD, including a history of prior major abdominal surgery. Prior major abdominal surgery is a concern for standard bedside or surgical catheter placement since these patients are at risk of having adhesions, which can complicate catheter placement. However, with laparoscopic advancements, prior major abdominal surgery is no longer even a relative contraindication to PD for skilled and experienced surgeons. We report the case of a male in his 70s with a history of cystoprostatectomy which was curative for a muscle invasive bladder carcinoma 5 years prior to his RRT. The patient had longstanding chronic kidney disease which worsened gradually. After receiving RRT education, the patient favoured PD. The catheter was placed despite the surgeon noting abdominal adhesions and the patient successfully underwent 12 months of PD which had a positive impact on his quality of life. He transferred to HD after contracting a complex PD-associated peritonitis. Thus, new research should be conducted to better understand the real impact of prior abdominal surgeries as a contraindication to PD, especially in centres where the surgeons have experience with advanced laparoscopy.